Guided relaxation-based virtual reality versus distraction-based virtual reality or passive control for postoperative pain management in children and adolescents undergoing Nuss repair of pectus excavatum: protocol for a prospective, randomised, controlled trial (FOREVR Peds trial). Issue 12 (30th December 2020) - Olbrecht, Vanessa A; Williams, Sara E; O'Conor, Keith T; Boehmer, Chloe O; Marchant, Gilbert W; Glynn, Susan M; Geisler, Kristie J; Ding, Lili; Yang, Gang; King, Christopher D
Abstract : Introduction: Virtual reality (VR) offers an innovative method to deliver non-pharmacological pain management. Distraction-based VR (VR-D) using immersive games to redirect attention has shown short-term pain reductions in various settings. To create lasting pain reduction, VR-based strategies must go beyond distraction. Guided relaxation-based VR (VR-GR) integrates pain-relieving mind–body based guided relaxation with VR, a novel therapy delivery mechanism. The primary aim of this study is to assess the impact of daily VR-GR, VR-D and 360 video (passive control) on pain intensity. We will also assess the impact of these interventions on pain unpleasantness, anxiety and opioid and benzodiazepine consumption. The secondary aim of this study will assess the impact of psychological factors (anxiety sensitivity and pain catastrophising) on pain following VR. Methods and analysis: This is a single centre, prospective, randomised, clinical trial. Ninety children/adolescents, aged 8–18 years, presenting for Nuss repair of pectus excavatum will be randomised to 1 of 3 study arms (VR-GR, VR-D and 360 video). Patients will use the Starlight Xperience (Google Daydream) VR suite for 10 min. Patients randomised to VR-GR (n=30) will engage in guided relaxation/mindfulness with the Aurora application. Patients randomised to VR-D (n=30) will play 1 of 3 distraction-based games, and those randomised to the 360 video (n=30) will watch the Aurora application without audio instructions or sound. Primary outcome is pain intensity. Secondary outcomes include pain unpleasantness, anxiety and opioid and benzodiazepine consumption. Ethics and dissemination: This study follows Standard Protocol Items: Recommendations for Interventional Trials guidelines. The protocol was approved by the Cincinnati Children's Hospital Medical Center's institutional review board. Patient recruitment began in July 2020. Written informed consent will be obtained for all participants. All information acquired will be disseminated via scientific meetings and published in peer-reviewed journals. Trial registration number: NCT04351776 .